Analisis Vitamin B6 (Piridoksin) pada Sediaan Tablet Multivitamin Neurotropik Menggunakan Spektrofotometri UV-Vis - Maritha, Vevi (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2019)
Vitamin B6 analysis in neurotrophic multivitamin tablet preparations requires a simple, fast and cheap method. UV-Vis spectrophotometer is having these criteria. Vitamin B6 analysis using UV Vis spectrophotometry is very quick so that the substance degradation can be inhibited and the results obtained will be accurate. Selection of single maximum wavelength for vitamin B6 will be able to separate with other components of vitamins B1 and B6 although all three are soluble in water. The optimal condition of vitamin B6 analysis in neurotropic multivitamin samples was using UV-Vis spectrophotometry at 325 nm wavelength. The solvent used is water. The calibration result curve in series of 60 ppm, 70 ppm, 80 ppm, 90 ppm, 100 ppm, 110 ppm, 120 ppm and 130 ppm have r value of 0, 9965. Determination of vitamin B6 levels using three brands of neurotrophic multivitamin samples performed. The measured theoretical level was 100 ppm, whereas the recovery of neurotropic multivitamin A samples were 98.24 ppm, 95 ppm and 95.78 ppm respectively with SD 1.69. The theoretical content of vitamin B6 in the neurotrophic multivitamin sample of B brand was 100 ppm, whereas the recovery was 99 ppm, 102 ppm and 98 ppm with SD 1.15. Determination of vitamin B6 concentration in the neurotropic multivitamin brand C the measured theoretical level was 100 ppm, while the recovery was 102 ppm, 101 ppm and 99 ppm with SD value of 1.53. The recovery of vitamin B6 level determination has been in accordance with AOAC requirements, ie for 100% ppm% analytical calculation 90-107%. The primary SD values of the three neurotrophic multivitamin samples of less than 2 indicate that vitamin B6 levels are acceptable. The results of this study indicate that vitamin B6 in a neurotrophic multivitamin sample can be analyzed using UV-VIS spectrophotometry at a wavelength of 325 nm using a water solvent.